2016
DOI: 10.1118/1.4961012
|View full text |Cite
|
Sign up to set email alerts
|

Time‐integrated activity coefficient estimation for radionuclide therapy using PET and a pharmacokinetic model: A simulation study on the effect of sampling schedule and noise

Abstract: (68)Ga-DOTATATE-PET measurements could possibly be used to predict the TIACs of (90)Y-DOTATATE when using a PBPK model and population-based Bayesian parameters. The two time-point measurement at 1 and 4 h p.i. with a noise up to FSD = 1% allows an accurate prediction of the TIACs in kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Receptor-targeted image-guided radionuclide therapy is increasingly recognized as a promising approach to treating cancer. (Bartlett, 2016; Hardiansyah et al, 2016; Iagaru et al, 2016; Jin et al, 2016; Kratochwil et al, 2016a; Kratochwil et al, 2016b; Kwekkeboom and Krenning, 2016; Li et al, 2016; Lo Russo et al, 2016; Nonnekens et al, 2016; Norain and Dadachova, 2016; Otte, 2016; Takahashi et al, 2016; Weber and Morris, 2016; Werner et al, 2016; Zukotynski et al, 2016) In particular, the potential for clinical translation of receptor-targeted alpha-particle (α-) therapy is receiving considerable attention; and several recent works have highlighted the potential advantages of α -therapy. (Bartlett, 2016; Iagaru et al, 2016; Kratochwil et al, 2016a; Kratochwil et al, 2016b; Kwekkeboom and Krenning, 2016) Alpha emitters are emerging as an attractive alternative (to α-emitters) due to higher linear-energy transfer (LET) (100 keV/μm) and resultant-significant increase in the intensity of ionizations (primary and secondary) along the relatively short path length that α-particles travel in tissue (compared to β-particles).…”
Section: Introductionmentioning
confidence: 99%
“…Receptor-targeted image-guided radionuclide therapy is increasingly recognized as a promising approach to treating cancer. (Bartlett, 2016; Hardiansyah et al, 2016; Iagaru et al, 2016; Jin et al, 2016; Kratochwil et al, 2016a; Kratochwil et al, 2016b; Kwekkeboom and Krenning, 2016; Li et al, 2016; Lo Russo et al, 2016; Nonnekens et al, 2016; Norain and Dadachova, 2016; Otte, 2016; Takahashi et al, 2016; Weber and Morris, 2016; Werner et al, 2016; Zukotynski et al, 2016) In particular, the potential for clinical translation of receptor-targeted alpha-particle (α-) therapy is receiving considerable attention; and several recent works have highlighted the potential advantages of α -therapy. (Bartlett, 2016; Iagaru et al, 2016; Kratochwil et al, 2016a; Kratochwil et al, 2016b; Kwekkeboom and Krenning, 2016) Alpha emitters are emerging as an attractive alternative (to α-emitters) due to higher linear-energy transfer (LET) (100 keV/μm) and resultant-significant increase in the intensity of ionizations (primary and secondary) along the relatively short path length that α-particles travel in tissue (compared to β-particles).…”
Section: Introductionmentioning
confidence: 99%
“…PBPK models have been proven to be a powerful method to analyse, simulate and predict the biodistribution of radiolabelled substances (10)(11)(12)(13)(14)(15)(16)(17)(18). The effect of different biodistributions during pre-therapeutic and therapeutic stage can be included in the PBPK model.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…Individual TIACs are usually determined by fitting the biokinetic data with a sum of exponential functions 12,13 or a physiologically based pharmacokinetic (PBPK) model. 8,14 Previously, we showed that the implementation of a PBPK model for dosimetry has advantages over the sum of exponential functions in the number of data per fitted parameter. 15 Furthermore, PBPK models have been shown to be a powerful tool to simulate the biokinetics of radiolabeled drugs and to predict both organ TIACs and ADs during peptide-receptor radionuclide therapy, radioimmunotherapy and radioligand therapy.…”
Section: Introductionmentioning
confidence: 99%
“…3,9,16,17 Unlike the sum of exponential functions, PBPK models include anatomical and physiological relevant mechanisms, such as the distribution of drugs via blood flow, specific binding, internalization, and release of drug from the cells, excretion, and physical decay. 3,14,18,19 Therefore, by using PBPK models, the determination of the interindividual variability of TIACs and AD can be explained by parameters of the subject (anatomical and/or physiological) and/or the drug. A strategy to individualize treatment is therefore to investigate the source of the interindividual TIACs variability in terms of subject and drug parameters using a PBPK model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation